Predicting of Shallow Slope Failure Using Probabilistic Model: a Case Study of Granitic Fill Slope in Northern Thailand - Agus Settyo Muntohar, A. Jotisankasa, H.J. Liao, R.M.N. Barus (Kasetsart University, 2015)
Slope failure occurred during rainfall in September 2009 near the peak of Doi-Inthanon national Park, Northern Thailand. Progressive studies have been conducted to monitor the pore water pressure variation during the monitored rainfall in September 2011. Lack of data for back analysis generated uncertainties in slope failure analysis. This paper presents probability analysis of the slope failures. The analysis considers the uncertainties of the influencing factor such as rainfall intensity, hydraulic and strength parameter of the soil. The probability analysis was calculated using Monte Carlo Simulation method (MCS). The slope failure was modeled using the infinite slope. Infiltration analysis was analyzed using Green – Ampt model. Three models of the rainfall hyetographs, including hourly rainfall, 15 minutes rainfall, and 5 minutes rainfall, were used to analysis the probability of failure. The simulation results show that the probability of failure (Pf) ranges about 0.36-0.38 for the corresponding rainfall. The highest probability of failure was obtained when daily rainfall was simulated. The probability of failure was strongly affected by the variability of the input parameter.